Eosinophilic Esophagitis-Associated Chemical and Mechanical Microenvironment Shapes Esophageal Fibroblast Behavior. Issue 2 (August 2016) - Muir, Amanda B.; Dods, Kara; Henry, Steven J.; Benitez, Alain J.; Lee, Dale; Whelan, Kelly A.; DeMarshall, Maureen; Hammer, Daniel A.; Falk, Gary; Wells, Rebecca G.; Spergel, Jonathan; Nakagawa, Hiroshi; et al.
ABSTRACT: Objectives: Eosinophilic esophagitis (EoE) is an immune-mediated allergic disease characterized by progressive esophageal dysmotility and fibrotic stricture associated with chronic esophageal fibroblast activation. It remains unknown how esophageal fibroblasts respond to EoE-relevant matrix stiffness or inflammatory cytokines. Methods: Immunofluorescence was used to evaluate α-smooth muscle actin (α-SMA) expression in endoscopic esophageal biopsies. Primary esophageal fibroblasts from adult and pediatric patients with or without EoE were exposed to transforming growth factor (TGF)β to determine gene expression, collagen-matrix contractility, and cytoskeletal organization. The influence of matrix stiffness upon fibroblast behavior was assessed on the engineered surface of polyacrylamide gels with varying stiffness. Fibroblast traction forces were measured using microfabricated-post-array-detectors. Results: EoE esophageal fibroblasts had enhanced α-SMA expression. TGFβ not only stimulated enhanced fibroblast-specific gene expression but also promoted fibroblast-mediated collagen-matrix contraction, despite disease state or age of patients as the origin of cells. Unlike conventional monolayer cell, culture conditions using plastic surface (1 GPa) that activates fibroblasts constitutively, our engineered platforms recapitulating physiologically relevant stiffness (1–20 kPa) revealed that matrix stiffness defines the extent of α-SMA expression, intracellular collagen fibril organization, SMAD3 phosphorylation, and fibroblast traction force. Conclusions: Matrix stiffness may critically influence TGFβ-mediated gene expression and functions of esophageal fibroblasts ex vivo independent of age and disease conditions. These findings provide a novel insight into the pathogenesis of fibrostenotic disease in EoE.